2014
DOI: 10.1063/1.4891636
|View full text |Cite
|
Sign up to set email alerts
|

Gain and tuning characteristics of mid-infrared InSb quantum dot diode lasers

Abstract: There have been relatively few reports of lasing from InSb quantum dots (QDs). In this work, type II InSb/InAs QD laser diodes emitting in the mid-infrared at 3.1 μm have been demonstrated and characterized. The gain was determined to be 2.9 cm−1 per QD layer, and the waveguide loss was ∼15 cm−1 at 4 K. Spontaneous emission measurements below threshold revealed a blue shift of the peak wavelength with increasing current, indicating filling of ground state heavy hole levels in the QDs. The characteristic temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A blueshift of the QD emission peaks is observed as the current is increased. Such blueshifts in type II QD systems are attributed to the combination of occupation of excited states and capacitive coulomb charging, rather than to the band bending at the type II interface 6 . At 4 K, the peaks from InAs are much stronger than the InSb QD peaks which is opposite to that observed in photoluminescence (PL) 7 .…”
Section: Insb/inas Qd Electroluminescencementioning
confidence: 95%
“…A blueshift of the QD emission peaks is observed as the current is increased. Such blueshifts in type II QD systems are attributed to the combination of occupation of excited states and capacitive coulomb charging, rather than to the band bending at the type II interface 6 . At 4 K, the peaks from InAs are much stronger than the InSb QD peaks which is opposite to that observed in photoluminescence (PL) 7 .…”
Section: Insb/inas Qd Electroluminescencementioning
confidence: 95%
“…Assuming the QD was composed of pure InSb, it was found from both k.p modeling in [16] and COMSOL calculation from Figure 3a that, to achieve typical transition energy of 0.35 eV, the QD height needed to be about 1.0 nm and radius 1.25-1.5 nm. However, high resolution microscopic images reported in [17] revealed that the QDs could possibly be much larger in size (~3 nm base radius and ~2.5 nm in height). The most probable reason for this disagreement is that instead of pure InSb, the QDs may contain a large proportion of As.…”
Section: Gain From Insb Qdsmentioning
confidence: 99%
“…The most probable reason for this disagreement is that instead of pure InSb, the QDs may contain a large proportion of As. By fixing the QD size according to the microscopic image in [17], the transition energy dependence on the composition of As was also calculated by the same method in COMSOL and plotted in Figure 3b. To obtain the 0.35 eV transition energy, the QD composition should be close to InAs0.6Sb0.4.…”
Section: Gain From Insb Qdsmentioning
confidence: 99%
“…14 Initial works on the growth of a thin InSb layer on InAs have demonstrated promising results in light-emitting diodes 15 and lasers. 16 More recently, efforts have been made to tune the strain and extend the emission wavelength by adding Gallium (Ga) to form an In x Ga 1Àx Sb thin layer on the InAs matrix for photodetector applications. 17,18 However, the photodetectors based on this material system are facing more challenges and therefore still have limited performance in recent reports.…”
mentioning
confidence: 99%